Structural-linguistic approach to assessment of functional states of organism of elite sportsmen, who have symptoms of chronic tiredness - Alwani. Abdulrahman (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: assessment of functional states of sportsmen's, having symptoms of chronic tiredness, organism with the help of structural-linguistic approach. Material: Sportsmen of different kinds of sports participated in the research. For determination of degree of chronic tiredness questionnaire by Leonova was applied. For classification of functional states of sportsmen's organism structural-linguistic approach was applied. Results: in 41% of the questioned sportsmen chronic tiredness was found. Appearance of their not stable states can be caused by reduction of organism's resistance to loads and high risk of chronic tiredness syndrome. Conclusions: in sportsmen with chronic tiredness we observed functional tension of organism's regulatory systems in rest and over-tension - after loads. We determined types of functional states of sportsmen's with chronic tiredness organism.